Morphological parameters affecting false lumen thrombosis following type B aortic dissection: a systematic study based on simulations of idealized models - Jafarinia, Alireza; Melito, Gian Marco; Müller, Thomas Stephan; Rolf-Pissarczyk, Malte; Holzapfel, Gerhard A.; Brenn, Günter; Ellermann, Katrin; Hochrainer, Thomas (Biomechanics and Modeling in Mechanobiology, 2023)
Type B aortic dissection (TBAD) carries a high risk of complications, particularly with a partially thrombosed or patent false lumen (FL). Therefore, uncovering the risk factors leading to FL thrombosis is crucial to identify high-risk patients. Although studies have shown that morphological parameters of the dissected aorta are related to FL thrombosis, often conflicting results have been reported. We show that recent models of thrombus evolution in combination with sensitivity analysis methods can provide valuable insights into how combinations of morphological parameters affect the prospect of FL thrombosis. Based on clinical data, an idealized geometry of a TBAD is generated and parameterized. After implementing the thrombus model in computational fluid dynamics simulations, a global sensitivity analysis for selected morphological parameters is performed. We then introduce dimensionless morphological parameters to scale the results to individual patients. The sensitivity analysis demonstrates that the most sensitive parameters influencing FL thrombosis are the FL diameter and the size and location of intimal tears. A higher risk of partial thrombosis is observed when the FL diameter is larger than the true lumen diameter. Reducing the ratio of the distal to proximal tear size increases the risk of FL patency. In summary, these parameters play a dominant role in classifying morphologies into patent, partially thrombosed, and fully thrombosed FL. In this study, we point out the predictive role of morphological parameters for FL thrombosis in TBAD and show that the results are in good agreement with available clinical studies.
Created from Fastlane, Scopus look-up
Keywords: Aortic dissection; Global sensitivity analysis; Morphological parametrization; Thrombus classification; Thrombus formation